Activities of Students During Learning Process in Mobile Learning Based on Android Package Kit - Handayani, Wahyuni; Malik, Adam; Munifah Assani, Qorry (KnE Social Sciences, 2024)
The current outbreak of COVID-19 has affected lives including closure of educational institutions. Based on Android Package Kit (APK), developed by authors, a learning multimedia-interactive can be accessed as a whole learning activity by the students, including the worksheet. The instrument used to collect data in this study is a worksheet that is integrated in the APK This worksheet is used to monitor students involvement and comprehension during mobile learning process. Students’ engagement of learning process on sound waves topic is measured manually based on the analysis of their written answers against the worksheet. In this study, 12 boys and 23 girls student of class XI answered the questions in worksheet to exceed passing score in sound waves concept during learning process. Based on the results of the study, it can be concluded that learning by using worksheets integrated into an APK can attract students’ interest to access it and increase student involvement in the learning process. Keywords: activities of students, learning process, mobile learning, android package Kit